2020
DOI: 10.1038/s41598-020-57927-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lymphotoxin-a (LTA) rs909253 A/G gene polymorphism, plasma level and risk of ankylosing spondylitis in a Chinese Han population

Abstract: Lymphotoxin-a (LTA) may be associated with the pathogenesis of inflammatory diseases. To assess the association of the LTA rs909253 A/G polymorphism with plasma level and risk of ankylosing spondylitis (AS) in a Chinese Han population. Genotyping and LTA plasma were tested by mass spectroscopy and enzyme-linked immunosorbent assay (ELISA), respectively. The results showed that the average plasma level of LTA in AS was significantly lower than in the controls (P = 0.000). Our results also indicated that LTA rs9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the absence of LTA or its receptor LTβR signi cantly impacts the development of lymphoid organs [52], while maintaining effective lymphoid tissue structure may aid in appropriate immune surveillance and in ammation regulation. In autoimmune diseases like ankylosing spondylitis, patients have been found to exhibit lower levels of plasma LTA [53]. On the other hand, activation of LTβR on the surface of stromal cells leads to the production of chemokines and cell adhesion molecules [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, the absence of LTA or its receptor LTβR signi cantly impacts the development of lymphoid organs [52], while maintaining effective lymphoid tissue structure may aid in appropriate immune surveillance and in ammation regulation. In autoimmune diseases like ankylosing spondylitis, patients have been found to exhibit lower levels of plasma LTA [53]. On the other hand, activation of LTβR on the surface of stromal cells leads to the production of chemokines and cell adhesion molecules [49].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association research has shown an abundance of additional loci ( 13 ), including ERAP1 and interleukin-23 receptor (IL-23R). HLA-B27 poses the highest risk and is identified in 90% of AS patients.…”
Section: The Role Of Hla-b27 In Asmentioning
confidence: 99%
“…It can help communicate lymphocytes and stromal cells and subsequently induce cancer cells cytotoxicity. 8,11,12 LTA has been implicated in the pathogenesis of acute and chronic HCV infection. [13][14][15] As an important mediator of hepatic fibrogenesis, TNF-β is released by lymphocytes (T cells, B cells, and natural killer cells) as an inflammatory response in chronic HCV patients.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Several studies examined the role of LT-α polymorphism in different immune-mediated diseases and it has been associated with diseases such as rheumatoid arthritis, 18 systemic lupus erythematosus, 19 cardiac diseases, 20,21 and ankylosing spondylitis. 12 Several polymorphisms of the LT-α gene were identified and Messer first reported the existence of a single nucleotide polymorphism (SNP) in the intron of LT-α at position 252 (G>A, designated rs909253, which is associated with overexpression of LT-α. 22 As lymphotoxin α is an important mediator of hepatic fibrogenesis, it may be helpful to elucidate the contribution of LTA gene polymorphism in different stages of CHC infection.…”
Section: Introductionmentioning
confidence: 99%